MATERIALS AND COMPONENTS FOR electronics and superconductor TECHNIQUE. Technology, PROPERTIES and application - L. M. Lynkou; V. A. Bogush; T. V. Borbotko; N. V. Nasonova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The main results of development and investigation of materials, components and elements for nanoelectronics, microelectronics and radioelectronics are reported. The original advances are summarized in the areas of superconductive electronics, nanostructured materials for VLSI, sol-gel techniques of isolating layers forming on the basis of hard-melting metallic oxides, metal SHF-plasma deposition of films, technologies of wideband electromagnetic shields forming and technical facilities of acoustic signals suppression.